Cumulative Effect of Pressing and Drying on Stress Generation within a Green Ceramic Compact. (7th April 2014) - Vidal-Sallé, E.; Falgon, D.; Peczalski, R.; Boyer, J-C.
Abstract : The internal stress field induced by uniaxial pressing and subsequent convective drying of a green ceramic powder was simulated by the finite element method. A density dependent elastoplastic constitutive law was used for the mechanical modeling of the compaction. A diffusive water transfer equation and a purely elastic behavior with imposed hydrostrain involving shrinkage were applied for the modeling of the drying process. The key material properties (hydrodiffusivity, hydrocontraction coefficient, Young's modulus, Poisson's ratio, and yield surface parameters) had been experimentally measured and introduced as functions of material density and water content. If residual stresses due to the compaction operation were taken into account, the maximum value of the tensile stress at the top external edge of the wheel and at the beginning of the drying process was two times higher than for a stress free green ceramic compact. Beyond the residual stress onset, the compaction operation induced density heterogeneities which had important consequences on the mechanical behavior of the compact.